Perissomyrmex Snyderi (Hymenoptera: Formicidae) is Native to Central America and Exhibits Worker Polymorphism - J. T. Longino; D. A. Hartley (Psyche: A Journal of Entomology)
The rediscovery of Perissomyrmex snyderi, previously known from the two worker types, is reported. New collections were observed from two different cloud forest sites in the state of Chiapas, Mexico. Based on the collection localities and cloud forest habitats, the species is clearly native to Central America. A sample of 205 workers revealed diphasic allometry, with distinct minor and major worker castes, and the queen was observed for the first time.